Multilevel National Analysis of Nursing Students' Perceived Opportunity to Access Evidence‐Based Tools During Their Clinical Learning Experience. Issue 6 (17th October 2018) - Palese, Alvisa; Gonella, Silvia; Grassetti, Luca; Destrebecq, Anne; Mansutti, Irene; Terzoni, Stefano; Zannini, Lucia; Altini, Pietro; Bevilacqua, Anita; Brugnolli, Anna; Dal Ponte, Adriana; De Biasio, Laura; et al.
Abstract: Background: Easy‐to‐access tools have been demonstrated to improve evidence‐based practice (EBP) competences among nursing students. However, students' perception of access to EBP tools (e.g., clinical practice guidelines [CPGs], protocols) is unknown. Aims: To explore: (1) nursing students' opportunity to access EBP tools during their education, and (2) associated factors. Methods: A national cross‐sectional study including all Italian nursing programs. Nursing students were deemed eligible according to the following inclusion criteria: Those who (1) were attending or just ended their practical rotation lasting at least 2 weeks at the time of the survey, and (2) expressed through written informed consent their willingness to take part in the study. Participants were asked about their perceived opportunity to access EBP tools during their most recent clinical learning experience (from 0 – not at all to 3 – always ). A set of explanatory variables was collected at the individual, nursing program, and regional levels by using a questionnaire. Results: Nine thousand six hundred and seven (91.6%) out of 10, 480 nursing students took part in the study. Overall, 4, 376 (45.6%) students perceived not at all or only a small opportunity to access EBP tools during their most recent clinical rotation. In the multilevel analysis, factors promoting access were mainly set at the clinical learning environment level (high safety and nursing care quality, high self‐directed learning opportunities, high quality of the learning environment, and being supervised by a clinical nurse). In contrast, male gender and lower academic class were associated with a lower perception of accessibility to EBP tools. A consistent variability in the perceived opportunity to access EBP tools emerged across regions. Linking Evidence to Action: Evidence‐based decision‐making is increasingly expected from nurses. Therefore, nursing faculties should safeguard and continuously improve students' competence regarding EBP, by implementing strategies mainly at the nursing program and regional levels.